Review on Sources and Handling Method of Pesticide Residues in Animal Products - ., Indraningsih (Indonesian Animal Sciences Society, 2006)
Field studies and literature search showed that some pesticide residues either organochlorines (OC) or organophosphates (OP) were detected in animal products (meat and milk) . Pesticide residues in meat collected from West Java were detected at the level of 0 .8 ppb lindane and 62 ppb diazinon . While in meat from Lampung was detected at the level of 7 ppb lindane . 2 .7 heptachlor, 0 .8 endosulfan and 0 .5 ppb aldrin . Furthermore, pesticide residues were also detected in the milk collected from West, Central and East Java . The levels of lindane were 2,3 ; 15,9 ; 0,2 ppb ; heptachlor 8 ; 0 .4 and 0,05 ppb; diazinon 8 ; 0 and 1,8 ppb; CPM 0,4 ; 0,8 and 0 ppb ; endosulfan 0,1 ; 0,04 and 0,05 ppb for West, Central and East Java, respectively . The source of pesticide contamination in animal products is generally originated from feed materials, fodders . contaminated soils and water around the farm areas . Minimalization approach of pesticide residues in animal products could be conducted integratedly, such as through chemical process, biodegradation using microorganisms . Organic farming system is recognised as an alternative that may be applied to minimise contamination on agricultural land, eventually reducing pesticide residues in the agricultural products . Feeding with organic agricultural by-products with low pesticide residues appears to reduce pesticide residues in animal products . In order to eliminate pesticide contamination in soil, it has to be conducted progressively by implementing sustainable organic farming . Key words : Pesticide residues, meat, milk